Caveolin-1-Knockout Mouse as a Model of Inflammatory Diseases. (29th August 2018) - Codrici, Elena; Albulescu, Lucian; Popescu, Ionela Daniela; Mihai, Simona; Enciu, Ana-Maria; Albulescu, Radu; Tanase, Cristiana; Hinescu, Mihail E.
Abstract : Caveolin-1 (CAV1) is the scaffold protein of caveolae, which are minute invaginations of the cell membrane that are involved in endocytosis, cell signaling, and endothelial-mediated inflammation. CAV1 has also been reported to have a dual role as either a tumor suppressor or tumor promoter, depending on the type of cancer. Inflammation is an important player in tumor progression, but the role of caveolin-1 in generating an inflammatory milieu remains poorly characterized. We used a caveolin-1-knockout (CAV1 −/− ) mouse model to assess the inflammatory status via the quantification of the pro- and anti-inflammatory cytokine levels, as well as the ability of circulating lymphocytes to respond to nonspecific stimuli by producing cytokines. Here, we report that the CAV1 −/− mice were characterized by a low-grade systemic proinflammatory status, with a moderate increase in the IL-6, TNF- α, and IL-12p70 levels. CAV1 −/− circulating lymphocytes were more prone to cytokine production upon nonspecific stimulation than the wild-type lymphocytes. These results show that CAV1 involvement in cell homeostasis is more complex than previously revealed, as it plays a role in the inflammatory process. These findings indicate that the CAV1 −/− mouse model could prove to be a useful tool for inflammation-related studies.